INTRODUCTION - Ken HYLAND; Octavia-Raluca ZGLOBIU-SANDU; Andrada FĂTU-TUTOVEANU (Studia Universitatis Babeş-Bolyai. Philologia)
If you were asked to identify the single most important area of growth in language teaching and research in the last decade or so you would probably find it hard to look further than LSP. Languages for Specific Purposes is an approach to language education based on identifying the specific language features, discourse practices, and communicative skills of target groups, while recognizing the subject-matter needs and expertise of learners (Hyland, 2018). It is an area of endeavour which sees itself as sensitive to contexts of discourse and action, and which uses this to develop research-based pedagogies to assist academic study, occupational interaction and professional communication skills. It is this distinctive focus on the ways language is used in particular settings and specific groups which is its strength, and which has led us to collate this special issue of STUDIA UNIVERSITATIS BABEȘ-BOLYAI. Series PHILOLOGIA.